Adjuvant immunotherapy improves recurrence-free and overall survival following surgical resection for intermediate/advanced hepatocellular carcinoma a multicenter propensity matching analysis - Xu, Xiao; Wang, Ming-Da; Xu, Jia-Hao; Fan, Zhong-Qi; Diao, Yong-Kang; Chen, Zhong; Jia, Hang-Dong; Liu, Fu-Bao; Zeng, Yong-Yi; Wang, Xian-Ming; Wu, Han; Qiu, Wei; et al. (Frontiers in Immunology, 2024)
Background & Aims: The effectiveness of adjuvant immunotherapy to diminish recurrence and improve long-term prognosis following curative-intent surgical resection for hepatocellular carcinoma (HCC) is of increased interest, especially among individuals at high risk of recurrence. The objective of the current study was to investigate the impact of adjuvant immunotherapy on long-term recurrence and survival after curative resection among patients with intermediate/advanced HCC. Methods: Using a prospectively-collected multicenter database, patients who underwent curative-intent resection for Barcelona Clinic Liver Cancer (BCLC) stage B/C HCC were identified. Propensity score matching (PSM) analysis was used to compare recurrence-free survival (RFS) and overall survival (OS) between patients treated with and without adjuvant immune checkpoint inhibitors (ICIs). Multivariate Cox-regression analysis further identified independent factors of RFS and OS. Results: Among the 627 enrolled patients, 109 patients (23.3%) received adjuvant immunotherapy. Most ICI-related adverse reactions were grading I-II. PSM analysis created 99 matched pairs of patients with comparable baseline characteristics between patients treated with and without adjuvant immunotherapy. In the PSM cohort, the median RFS (29.6 vs. 19.3 months, P=0.031) and OS (35.1 vs. 27.8 months, P=0.036) were better among patients who received adjuvant immunotherapy versus patients who did not. After adjustment for other confounding factors on multivariable analyses, adjuvant immunotherapy remained independently associated with favorable RFS (HR: 0.630; 95% CI: 0.435-0.914; P=0.015) and OS (HR: 0.601; 95% CI: 0.401-0.898; P=0.013). Subgroup analyses identified potentially prognostic benefits of adjuvant immunotherapy among patients with intermediate-stage and advanced-stage HCC. Conclusion: This real-world observational study demonstrated that adjuvant immunotherapy was associated with improved RFS and OS following curative-intent resection of intermediate/advanced HCC. Future randomized controlled trials are warranted to establish definitive evidence for this specific population at high risks of recurrence.